Imidazoquines as Antimalarial and Antipneumocystis Agents - Nuno Vale (2009)
Peptidomimetic imidazolidin-4-one derivatives of primaquine (imidazoquines) recently displayed in vitro activity against blood schizonts of a chloroquine-resistant strain of Plasmodium falciparum. Preliminary studies with a subset of such imidazoquines showed them to both block transmission of P. berghei malaria front mouse to mosquito and be highly stable toward hydrolysis at physiological conditions. This prompted Lis to have deeper insight into the activity of imidazoquines against both Plasmodia and Pneumocystis carinii, on which primaquine is also active. Full assessment of the in vivo transmission-blocking activity of imidazoquines, in vitro tissue-schizontocidal activity on P. berghei-infected hepatocytes, and in vitro anti-P. carinii activity is now reported. All compounds were active in these biological assays, with generally lower activity than the parent drug. However, imidazoquines' stability against both oxidative deamination and proteolytic degradation suggest that they will probably have higher oral bioavailability and lower hematotoxicity than primaquine, which might translate into higher therapeutic indexes.